Pengembangan Multimedia Pembelajaran Menggunakan Lectora Inspire Berbasis Multipel Representasi pada Materi Kesetimbangan Kimia - Utami Widiyaningsih; Abdul Hadjranul Fatah; Syarpin Syarpin (Jurnal Ilmiah Kanderang Tingang, 2020)
This study aims to describe the content and quality of multimedia learning Lectora Inspire based on multiple representations of Chemical Equilibrium material. This multimedia development learning based on multiple representations uses the Four-D (4D) model adapted from Thiagarajan. This study is limited to the stages define (defining), design (design) and develop (development). The data needed is the suitability of the concept label with the 2013 curriculum syllabus, the suitability of learning multimedia content with the concept label, narrative and typology as well as the results of the trial. The instruments used to obtain the data are the concept label identification table with the 2013 curriculum syllabus, the concept label identification table, narrative and typology, the concept label conformity checklist, narrative and typology, and the response questionnaire. Product trials were conducted on the 2018 chemistry students to determine the feasibility of students for multimedia that had been developed. Multimedia learning based on multiple representations using lectora inspire consists of home pages, instructions for using multimedia, how to read navigation content and chemical equilibrium materials. The chemical equilibrium material content consists of fourteen concept labels. Multimedia learning based on multiple representations using Lectora Inspire on chemical equilibrium material is dominated by concept labels that include submicroscopic typology and symbolic chemical equilibrium about reaction processes microscopically. The average individual trial results are 87.2% and the average group trial results are 88.5%.